First description of feline inflammatory mammary carcinoma: clinicopathological and immunohistochemical characteristics of three cases - Pérez-Alenza, M Dolores (BioMed Central, 2004)
INTRODUCTION: Inflammatory breast cancer is a special type of locally advanced mammary cancer that is associated with particularly aggressive behaviour and poor prognosis. The dog was considered the only natural model in which to study the disease because, until now, it was the only species known to present with inflammatory mammary carcinoma (IMC) spontaneously. In the present study we describe clinicopathological and immunohistochemical findings of three cats with IMC, in order to evaluate its possible value as an animal model. METHODS: We prospectively studied three female cats with clinical symptoms of IMC, identified over a period of 3 years. Clinicopathological and immunohistochemical evaluations of Ki-67, and oestrogen, progesterone and androgen receptors were performed. RESULTS: All three animals presented with secondary IMC (postsurgical) characterized by a rapid onset of erythema, severe oedema, extreme local pain and firmness, absence of subjacent mammary nodules, and involvement of extremities. Rejection of the surgical suture was observed in two of the cats. Histologically, highly malignant papillary mammary carcinomas, dermal tumour embolization of superficial lymphatic vessels, and severe secondary inflammation were observed. The animals were put to sleep at 10, 15 and 45 days after diagnosis. Metastases were detected in regional lymph nodes and lungs in the two animals that were necropsied. All tumours had a high Ki-67 proliferation index and were positive for oestrogen, progesterone and androgen receptors. CONCLUSION: Our findings in feline IMC (very low prevalence, only secondary IMC, frequent association of inflammatory reaction with surgical suture rejection, steroid receptor positivity) indicate that feline IMC could be useful as an animal model of human inflammatory breast cancer, although the data should be considered with caution.